Effect of concentration and components of MS medium on in vitro germination of Ugni molinae - Rodríguez, Mario; Chacón, Manuel; Carrillo, Rubén (Bosque (Valdivia), 2017)
The objective of the study was to evaluate the effect of concentration and components of the Murashige and Skoog (MS) medium on in vitro germination of Ugni molinae. Two tests were performed; in the first one, different concentrations of the MS medium were used (full-strength MS, 1/2 MS, 1/4 MS, 1/8 MS and MS free). In the second experiment, one of the component was excluded (macro salts, micro salts or vitamins). A tetrazolium test was performed to assess viability. After the first two weeks of sowing, all treatments started germination, which was ascending until approximately 20 days, and then a slowdown was observed, which remained stable between days 40 and 60. All treatments containing any concentration of MS presented lower germination than that presented by the MS free medium, as the media containing some of its components, especially macro salts. The tetrazolium test showed 87 % of viability of the seeds: the maximum germination was 42%, which showed a strong latency. Germination of U. molinae is affected by the presence of the MS medium salts. Based on these results the use of only water and agar are recommended as the in vitro germination medium.